The Effect of Using Duolingo Application on Students’ Speaking Skill in Higher Education - Pipit Rahayu; Eripuddin Eripuddin; Ng Yu Jin; Bayu Arya Dinata (STAI Hubbulwathan Duri, 2025)
Speaking skill remains a core component of English language proficiency, yet many EFL learners struggle to develop it effectively through conventional instruction alone. This study investigates whether the use of the Duolingo application can enhance the speaking skills of fourth-semester students in the English Department at Pasir Pengaraian University. A quantitative, pre-experimental design was employed using a one-group pretest-posttest model. The participants consisted of 24 fourth-semester students selected through cluster total sampling. Students’ speaking skills were assessed before and after a treatment period involving the use of Duolingo as a supplementary learning tool. The findings revealed a notable improvement in students' speaking performance following the intervention. The average pretest score was 63.96 with a standard deviation of 18.11, which increased to 82.92 in the post-test with a standard deviation of 11.60. This improvement suggests a positive effect of Duolingo on students' speaking proficiency. The results indicate that mobile-assisted language learning applications such as Duolingo may serve as effective supplementary tools in higher education contexts. While the findings demonstrate short-term gains, further longitudinal research is necessary to evaluate the sustainability and broader applicability of these outcomes. Nonetheless, this study supports the integration of digital learning platforms into English language instruction to foster more engaging and autonomous learning experiences.